Pengaruh Pembangunan IKN (Ibu Kota Negara) Terhadap Populasi Primata Di Kalimantan Timur - Laila, Lailatur Rohmah (JURNAL ILMU PENDIDIKAN, 2024)
This article explores the impact of the development of the National Capital City (IKN) on the primate population in East Kalimantan. The main problem discussed was the need to protect the natural habitat of primates which is threatened due to infrastructure and housing development which destroys natural ecosystems. The aim of this research is to highlight the importance of protecting biodiversity and considering conservation issues in the planning and implementation of IKN development in the region. The method used in this research is literature study. The literature study method is a series of activities related to library data collection methods, from journals, books, mass media that support the writing of this article. This article focuses on previous research that describes threats to the survival of primates in East Kalimantan due to the destruction of their natural habitat. The research results show that the development of IKN in East Kalimantan has serious implications for primate populations, including species listed as threatened or vulnerable. This analysis emphasizes the need for effective conservation strategies and the implementation of regional planning that considers the development of wildlife corridors and protected areas to ensure the survival of primate populations and maintain the balance of the ecosystem in the region. In conclusion, this article encourages greater awareness of the need to protect natural primate habitats as well as the need for collaboration between the government, conservation institutions and other related parties to implement sustainable and environmentally friendly development plans in the East Kalimantan IKN area. This conclusion emphasizes the importance of maintaining a balance between economic development and environmental conservation to ensure the continuity of a balanced and sustainable ecosystem in East Kalimantan.